Identification of a highly lethal V3+TP53+ subset in ALK+ lung adenocarcinoma. Issue 1 (30th October 2018) - Christopoulos, P.; Kirchner, M.; Bozorgmehr, F.; Endris, V.; Elsayed, M.; Budczies, J.; Ristau, J.; Penzel, R.; Herth, F.J.; Heussel, C.P.; Eichhorn, M.; Muley, T.; et al.
Abstract : Tyrosine kinase inhibitors (TKI) have improved prognosis in metastatic anaplastic lymphoma kinase (ALK)‐driven lung adenocarcinoma, but patient outcomes vary widely. We retrospectively analyzed the clinical course of all cases with assessable baseline TP53 status and/or ALK fusion variant treated at our institutions ( n = 102). TP53 mutations were present in 17/87 (20%) and the echinoderm microtubule‐associated protein‐like 4 ( EML4 )‐ ALK variant 3 (V3) in 41/92 (45%) patients. The number of metastatic sites at diagnosis was affected more by the presence of V3 than by TP53 mutations, and highest with both factors (mean 5.3, p < 0.001). Under treatment with ALK TKI, progression‐free survival (PFS) was shorter with either TP53 mutations or V3, while double positive cases appeared to have an even higher risk (hazard ratio [HR] = 2.9, p = 0.015). The negative effect of V3 on PFS of TKI‐treated patients was strong already in the first line (HR = 2.5, p = 0.037) and decreased subsequently, whereas a trend for PFS impairment under first‐line TKI by TP53 mutations became stronger and statistically significant only when considering all treatment lines together. Overall survival was impaired more by TP53 mutations (HR = 4.9, p = 0.003) than by V3 (HR = 2.4, p = 0.018), while patients with TP53 mutated V3‐driven tumors carried the highest risk of death (HR = 9.1, p = 0.02). Thus, TP53 mutations and V3 are independently associated with enhanced metastatic spread, shorter TKI responses and inferior overall survival in ALK + lung adenocarcinoma. Both markers could assist selection of cases for more aggressive management and guide development of novel therapeutic strategies. In combination, they define a patient subset with very poor outcome. Abstract : What's new? This is the first study on the clinical impact of TP53 mutations in ALK‐driven lung adenocarcinoma that simultaneously considers the adverse effects of EML4 ‐ ALK fusion variant 3. Both molecular features are independently associated with more aggressive disease course, including metastases to more organs, shorter responses to tyrosine kinase inhibitors, and worse overall survival. Their effects appear to be synergistic, and double‐positive cases have a very poor outcome. Both markers could assist patient selection for more aggressive management and help develop novel therapeutic strategies.